EFFECTIVENESS OF COMBINED SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) AND LACTATION EDUCATION ON BREASTFEEDING SELF-EFFICACY AMONG POSTPARTUM MOTHERS: A QUASI-EXPERIMENTAL STUDY - Silvia Mona; Susanti (Pena Cendekia Insani, 2026)
Breastfeeding self-efficacy is a key determinant of successful exclusive breastfeeding and contributes to improved maternal and infant health outcomes. However, many postpartum mothers experience psychological and educational barriers that reduce confidence in breastfeeding, highlighting the need for effective supportive interventions. To evaluate the effectiveness of a combined Spiritual Emotional Freedom Technique (SEFT) and structured lactation education program on breastfeeding self-efficacy among postpartum mothers. A quasi-experimental pretest posttest control-group study was conducted involving 56 postpartum mothers recruited through purposive sampling and non-randomly allocated to an intervention group (n = 28) or a control group (n = 28). The intervention group received a combination of SEFT and structured lactation education, whereas the control group received standard postpartum care. Data were analyzed using analysis of covariance (ANCOVA), controlling for baseline self-efficacy scores. Following the intervention, breastfeeding self-efficacy was significantly higher in the intervention group than in the control group (p < 0.001), with a large effect size (Cohen’s d = 2.35). This association remained significant after adjustment for baseline self-efficacy, age, parity, education, and spousal support. The combination of SEFT and structured lactation education was associated with improved breastfeeding self-efficacy among postpartum mothers. As a low-cost psychosocial and educational intervention, this approach may strengthen maternal confidence in breastfeeding and support efforts to improve exclusive breastfeeding practices.